PROTECTION OF INFORMAL WORKERS AS PARTICIPANTS THROUGH THE MAGELANG REGIONAL SOCIAL SECURITY SYSTEM - Heniyatun, Heniyatun; Rusdjijati, Retno; Sulistyaningsih, Puji (Fakultas Hukum Universitas Muhammadiyah Magelang, 2018)
The purpose of this study is to review the rights of workers to obtain protection, including informal workers, as mandated in Article 3 paragraph (2) of Law Number 32 of 1992 concerning Labor Social Security that every worker has the right to social security of workers. The hazard risk from the work environment owned by informal workers is the same as that of formal workers. So far, the occupational health services provided are still curative, while health care and improvement efforts to improve work and preventive capacity are always neglected. This study uses a juridical empirical research method with a descriptive approach; data collection is done through questionnaires. The research sample includes workers in the home or micro industries both in the Regency and in the City of Magelang. Samples are collected using a nonprobability sampling method, then analyzed using qualitative analysis with inductive methods. Based on the results of the study, the understanding of the SJSN by both employers and informal sector workers is insufficient, but the majority of respondents have a desire to join the SJSN program, with the priority of health insurance and work accident insurance programs. The ability and willingness to become a BPJS participant are influenced by the level of income, and level of education. Current informal sector workers have not been covered by guaranteed protection, both BPJS Kesehatan, and BPJS. The main factor is the non-participation of casual workers in the guarantee of protection due to financial inability to pay contributions. Besides that, it was also because of his ignorance, even though it was not significant. This is due to a lack of socialization from stakeholders regarding the importance of health and safety guarantees and protection for workers and their families in addition to regulations that also do not accommodate informal workers.